2013
DOI: 10.1017/s1368980013002462
|View full text |Cite
|
Sign up to set email alerts
|

Dietary quality indices vary with sociodemographic variables and anthropometric status among Mexican adults: a cross-sectional study. Results from the 2006 National Health and Nutrition Survey

Abstract: Objective: To evaluate the dietary quality of Mexican adults' diet, we constructed three dietary quality indices: a cardioprotective index (CPI), a micronutrient adequacy index (MAI) and a dietary diversity index (DDI). Design: Data were derived from the 2006 National Health and Nutrition Survey, which is a national survey representative of the Mexican population with a stratified, multistage, probabilistic sample design. Dietary intake was assessed from an FFQ with 101 different foods and daily nutrient intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 45 publications
3
23
1
Order By: Relevance
“…Previous research has shown that dietary quality is affected not only by gender, but also by education, occupation, and income level [29,46]. In our study, we also found that the DQD scores were associated with these factors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous research has shown that dietary quality is affected not only by gender, but also by education, occupation, and income level [29,46]. In our study, we also found that the DQD scores were associated with these factors.…”
Section: Discussionsupporting
confidence: 83%
“…Previous research has also shown that 68.9% of older Chinese have an over-intake of cereal, with 25.6% of older people consuming an extreme surplus of cereals according to the China Health and Nutrition Study [28]. Energy consumption has decreased with the introduction of a modern lifestyle; dietary guidelines from most countries have either recommended decreasing the total amount of cereal or increasing whole grains [29,30,31,32]. However, dietary behaviors are difficult to change in a short time.…”
Section: Discussionmentioning
confidence: 99%
“…Although their conclusion was that (as for high-income countries) higher SEP individuals had higher quality diets overall, this was a reflection of the superior micronutrient content and diversity of their diets, even though they simultaneously consumed more energy, cholesterol, and saturated fats and fewer fibres [72]. The stage of transition to a more BWestern^diet pattern had an important influence on diet composition relative to SEP.…”
Section: Maternal Dietmentioning
confidence: 92%
“…In the southern region, for example, coverage of antihypertensive drugs should be expanded to reduce the high prevalence of adults with hypertension who are not undergoing this treatment [71]. On the other hand, the higher prevalence of hypercholesterolemia observed in this study is coupled with low-quality diets with greater energy density in the northern region [85,86]. This could be mitigated by improving the food environment, dietary recommendations, and increasing availability of and adherence to lipid-lowering treatment in this country area.…”
Section: Discussionmentioning
confidence: 85%